دراســــة إحصائية عن مدى انتشار سرطان عنق الرحم بمدينة صبراتة: دراسة ميدانية داخل المعهد القومي لعلاج الأورام صبراتة - هيفاء محمد المبروك; مراد الهادي كنان (Surman Journal of Science and Technology, 2025)
This study aims to identify the prevalence of cervical cancer within the National Cancer Institute in Sabratha. It also aims to determine the most common types of cervical cancer and the relationship between these types and age groups. The study employs an analytical approach using the Statistical Package for the Social Sciences (SPSS) version 25. Data related to cervical cancer were collected from the institute’s statistical records, showing its prevalence between 2020 and 2023. The study found that the highest percentage (37.8%) was in the 35-45 age group, followed by 27.2% of the sample aged 45-55. The highest incidence rate was in 2021 (38.7%), followed by 2022 (27.5%). It is evident that the highest incidence rate of cervical cancer was in 2020, reaching 41.86%. Furthermore, there is an inverse relationship between age and cervical cancer incidence; the older a woman is, the lower her likelihood of developing cervical cancer.